KOMODITI LOKAL POTENSIAL DI KAWASAN HIDROLOGI GAMBUT (KHG) KAHAYAN SEBANGAU KABUPATEN PULANG PISAU: Yuprin AD., Wilson Daud, Yanetri Asi, Johanna M. Rotinsulu, Zafrullah Damanik, Maria Haryulin Astuti., Inga Torang - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTActually, commodities that have been developed by communities were potential commodity because the communityhave considered the aspects of technical, economy and social. Nevertheless, some commodities developed by thesecommunities were still not optimal, thus it needs a feasible development model. The results showed that based onland type, local commodities in KHG Kahayan - Sebangau could be developed through three models, namely theintegration model of agro-silva-pastura-fishery on inland peat type, while in transition peat type was integration modelof agro-silva-pastura, and in coastal peat type was integration model of agro-silva-fishery.Keywords: Peat land, local commodities